Penggunaan Media Video dan Games Wordwall untuk Meningkatkan Keaktifan Siswa Kelas 8 pada Materi Kitab-kitab Allah - Sari, Putri Anggalia Puspita; Saputri, Nadia; Rafiq, Muhammad Ainur; Aziz, Abdul (Darul Yasin Al Sys, 2024)
This research departs from the lack of student activity in learning Islamic religious education. Because the lack of use of media in learning makes learning tend to be more boring and monotonous for students. To overcome these problems, it is necessary to develop interesting learning media that must be prepared according to the needs of students. The purpose of this research is to determine the development and feasibility of learning media, video media, and wordwall games on the material of believing in the books of Allah in grade VIII SMP NU Palangkaraya.This research is a research and development of Research and Development (R&D) which refers to the ADDIE development model which consists of five stages which include analysis, design, development, implementation and evaluation. The subjects of this study are media expert validators and material expert validators, using field trials applied to grade VIII students of SMP NU Palangkaraya.The results of this study are that video-based learning media products and wordwall games have been produced with assessments from material experts and media experts by material validators obtaining